Plants for the Future 2015
DOI: 10.5772/60873
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Parameters in Tomato Fruits from Different Cultivars as Functional Foods for Agricultural, Industrial, and Pharmaceutical Uses

Abstract: Tomato and tomato based products are an important agricultural production worldwide. More than 80 % of grown tomatoes in the worldwide are processing in the products such as tomato juice, paste, puree, catsup, sauce, and salsa. Tomato fruit is rich in phytochemicals and vitamins. Tomato nutritional value, color, fruit and flavor of their products depends mainly on lycopene, β-carotene, ascorbic acid and sugars and their ratio in fruits. Epidemiological studies and the results associated with the consumption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 83 publications
(100 reference statements)
1
27
2
Order By: Relevance
“…Tomato firmness under compression and skin puncture are mechanical properties relevant on characterization of processing tomatoes and are related to ripening rate and susceptibility to mechanical damage during harvest and transport (Li et al, 2017;Stropek & Golacki, 2015), taking into account that fruits are exposed to mechanical stress during those operations that can cause damage by cutting and/or crushing, and therefore causing qualitative and quantitative losses (Dimitrios et al, 2018;Viskelis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato firmness under compression and skin puncture are mechanical properties relevant on characterization of processing tomatoes and are related to ripening rate and susceptibility to mechanical damage during harvest and transport (Li et al, 2017;Stropek & Golacki, 2015), taking into account that fruits are exposed to mechanical stress during those operations that can cause damage by cutting and/or crushing, and therefore causing qualitative and quantitative losses (Dimitrios et al, 2018;Viskelis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The total concentration of lycopene, β carotene, and their isomers in concentrated extracts (oleoresins) of SCE-CO2 is depicted in Figure 3. Genotype differences between cultivars, such as skin thickness, skin/pulp ratio, seed numbers, and dimensions, could significantly affect the amounts of the freeze-dried tomato matrix obtained from fresh tomatoes [38,39]. The antioxidant properties of lipophilic extracts were determined and evaluated in SCE-CO2 extracts from different tomato varieties.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of different tomato genotypes it has been shown that cherry tomato contains the highest level of dry matter compared to other tomato hybrids (HALLMANN et al, 2007). The dry matter content ranged from 6.64% to 9.06% in the organic tomato production, and in the conventional production from 6.37% to 8.44% (VISKELIS, 2015).…”
Section: Table 3 Year and Hybrid Effects On Dry Matter Content In Tementioning
confidence: 99%